Epu Pullu, Epu Pillan and Other Sexuality-Affectivity Themes in the Mapuche Context: Approaching Poyewun - Millaleo-Hernandez, A (UNIV CATOLICA NORTE, 2022)
Using a video from social media about sexual diversity within the Mapuche people as a starting point, this article reflects on affectivity and sexuality in the contemporary Mapuche context. The video features the concepts of Epu Piillii and Epu Pillan and invites dialogue, creating tension around the feminine/masculine, the body, spirituality and, fundamentally, binary sex-uality. This article argues that these tensions are rooted in colonial masculinity pacts that make female and feminized bodies invisible within Mapuche society. It proposes the concept of Poyewiin as a vanishing point for these pacts, which, from a Mapuche epistemological perspec-tive, requires reviving the debate on love, advancing toward decolonization of spirituality and bodies in the reciprocity of affective bonds, which would enable the rejected bodies to emerge, forcing us to revisit Mapuche history and current affairs from our own perspective. To prepare this text, researchers held group and individual interviews with people who identify as Mapu-che and are recognized activists within the movement. These interviews were held face-to-face until the emergence of COVID-19 when researchers added an online modality.